2020
DOI: 10.2147/ijn.s263756
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bone-Targeted Extracellular Vesicles from Mesenchymal Stem Cells for Osteoporosis Therapy</p>

Abstract: Background: Current drugs used for osteoporosis therapy show strong adverse effects. Stem cell-derived extracellular vesicles (EVs) provide another choice for osteoporosis therapy. Mouse mesenchymal stem cells (mMSCs)-derived EVs promote bone regeneration; however, their clinical application is limited due to non-specific tissue targeting. Alendronate specifically targets bone tissue via hydroxyapatite. Therefore, EVs were combined with alendronate to generate Ale-EVs by "click chemistry" to facilitate EVs tar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 56 publications
2
32
0
1
Order By: Relevance
“… 51 In a previous study, the researchers observed that unless combined with alendronate, the mouse MSC-EVs did not target bone tissues. 52 This result was in line with that observed in this study, which showed that the exogenous WJ-MSC-EVs after systemic injection failed to target the femurs or other bond regions in OVX mice or the healthy mice group. This result was performed by IVIS fluorescent imaging after mice were systemically injected with DIR-labeled MSC-EVs.…”
Section: Discussionsupporting
confidence: 92%
“… 51 In a previous study, the researchers observed that unless combined with alendronate, the mouse MSC-EVs did not target bone tissues. 52 This result was in line with that observed in this study, which showed that the exogenous WJ-MSC-EVs after systemic injection failed to target the femurs or other bond regions in OVX mice or the healthy mice group. This result was performed by IVIS fluorescent imaging after mice were systemically injected with DIR-labeled MSC-EVs.…”
Section: Discussionsupporting
confidence: 92%
“…EVs from mouse vascular endothelial cells are enriched in miR-155, exhibiting protective effects on bone in an ovariectomized (OVX) mice model of menopausal osteoporosis [165]. The pro-osteogenic potential of EVs released by mouse MSCs was specifically addressed to the bone by linking the murine MSC-derived EVs with alendronate [166]. These bone-targeting EVs were effective in protecting bone of OVX mice.…”
Section: Discussionmentioning
confidence: 99%
“…This allows EV surface functionalization for delivery of small molecules, large biomacromolecules, and polymers without altering particle size or function. Murine MSC-derived EVs were modified by copper-free click chemistry to generate an Ale-EVs system (EVs coupled with Alendronate, a medication used for osteoporosis) administered to an in vivo model of ovariectomy (OVX)-induced osteoporosis ( Wang Y. et al, 2020 ). These Ale-EVs had an affinity to bone tissue and promoted regeneration under osteoporotic conditions with low toxicity.…”
Section: Engineered Evsmentioning
confidence: 99%
“…In addition to cargo loading via surface conjugation ( Wang Y. et al, 2020 ), other strategies used to load cargo into EVs include parental cell modification, passive diffusion, and active loading. Overexpression of components in parental cells is an effective way to increase abundance in resulting EVs for greater function.…”
Section: Engineered Evsmentioning
confidence: 99%